Simultaneously carbonized and sulfonated sugarcane bagasse as solid acid catalyst for the esterification of oleic acid with methanol. (January 2019) - Flores, Ken P.; Omega, Jan Laurence O.; Cabatingan, Luis K.; Go, Alchris W.; Agapay, Ramelito C.; Ju, Yi-Hsu
Abstract: Solid acid catalyst was synthesized from sugarcane bagasse, a residue left behind during sugar milling, through a simpler and less energy-intensive one-step process, simultaneous carbonization-sulfonation. A range of synthesis temperature (150, 200, 250 °C) and time (4, 6, 8 h) were investigated in the preparation of the catalyst to determine their effects on the catalytic activity and conversion during esterification of oleic acid and methanol. Extensive washing of the freshly synthesized catalyst have significant influence on the performance of the catalyst, as loosely bound acid sites are removed in the process lowering its activity but improving its stability. The catalyst synthesized at 150 °C for 8 h, having a sulfonic acid density of 0.59 mmol/g, exhibited the best performance during a 4-h esterification assay using oleic acid and methanol, resulting in an FFA conversion of 46.5% and catalytic activity of 4.62 mmol oleic acid/mmol-SO3 H ·h. Additionally, the catalyst could be used for at least five 24-h esterification cycles, where an FFA conversion of as high as 87% was achieved. The catalyst retained 76.5 and 86% of its initial catalytic performance and sulfonic acid density, respectively, after the fourth cycle, offering good operational stability. Highlights: One-step synthesis of carbon-based solid acid catalyst using sugarcane bagasse as raw material. Simultaneous carbonization and sulfonation at moderate synthesis temperature (150 °C) and time (8 h). Exhaustive washing of synthesized catalyst with water for reliable and stable catalytic activity.